Asphalt powder fiber cement-based composite material
By introducing asphalt powder fiber cement-based composite materials into cement-based materials, combined with VAE latex powder and phthalate coupling agent, the problems of insufficient bending toughness and waterproof and corrosion resistance of traditional cement-based materials are solved, and better bending is achieved Performance and durability.
Patent Information
- Application Number
- CN202411262242.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
AI Technical Summary
Traditional cement-based materials have shortcomings in bending toughness, waterproofing and corrosion resistance, especially the problem of low bending strength, which needs further improvement.
The bending performance, waterproof and impermeable properties of the composite material are optimized by adjusting the ratio of raw materials, including fibers, asphalt powder, VAE latex powder and phthalate coupling agent.
The bending performance, waterproof and corrosion resistance of composite materials are improved, construction ease and durability are enhanced, and the overall performance of the material is improved through the synergy between fiber dispersion and bonding strength.
Smart Images

Figure BDA0005036060730000051 
Figure BDA0005036060730000071 
Figure BDA0005036060730000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cement-based composite materials, and in particular relates to an asphalt powder fiber cement-based composite material with good bending performance, impermeability and corrosion resistance. Background Art
[0002] As the most widely used material in construction projects, cement-based materials have a series of advantages such as low cost and excellent mechanical properties. However, they also have the defects of poor toughness and average impermeability and corrosion resistance. At present, traditional cement-based reinforcement and repair materials have the problems of poor bending toughness, average waterproof and corrosion resistance. The polymer-modified cement-based materials can be significantly improved in bending toughness, waterproof and impermeability, but still have the defect of low bending strength, which still needs further improvement and optimization. Summary of the invention
[0003] In view of this, in order to solve the above-mentioned technical problems, the present invention proposes an asphalt powder fiber cement-based composite material with good bending performance, impermeability and corrosion resistance. Through the compounding of multiple raw materials, the bending performance, waterproof impermeability and corrosion resistance of the composite material are effectively optimized and improved.
[0004] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0005] An asphalt powder fiber cement-based composite material, the raw material components include fibers and powder materials, the weight of the fibers is 0.5% to 2% of the weight of the powder materials; the powder materials include the following components by mass percentage: 0.25% to 2.5% asphalt powder, 40% to 60% cement, 30% to 50% river sand, 5% to 25% fly ash, 0.1% to 0.5% water reducer, 0.25% to 1.0% VAE latex powder, and 0.1% to 1.0% phthalate coupling agent.
[0006] High-tenacity fibers can improve the crack resistance, fatigue resistance, bending toughness and compressive deformation capacity of composite materials. Different types of fibers have different properties such as tensile strength, elongation at break, elastic modulus and hydrophilicity. Therefore, different types of asphalt powder fiber cement-based composite materials can achieve good performance indicators in different application occasions by adjusting the powder material mix ratio.
[0007] Asphalt powder can improve the dispersion performance, construction and workability of high-tenacity fibers in composite materials after adding water and stirring: Asphalt powder has a certain hydrophobicity after being dispersed in water. After being evenly mixed with other powder materials and stirred with water, it can reduce the slurry viscosity and increase the repulsion between high-tenacity fibers. It can improve the dispersion performance of fibers in composite materials, and at the same time reduce the consistency of composite materials after adding water and stirring, prolong the coagulation time, thereby improving construction and workability;
[0008] Asphalt powder can improve the corrosion resistance of composite materials: after the composite materials are stirred and formed with water, the asphalt powder in them forms a certain film with the hydration reaction of the cementitious material and combines with the hydration product of the cementitious material to effectively seal the internal voids of the composite materials, thereby improving the composite materials' impermeability and durability such as resistance to sulfate erosion, carbonization, chloride ion penetration, and freeze-thaw cycles;
[0009] Asphalt powder can improve the bending properties of composite materials: when the composite material is deformed by pressure, asphalt powder can improve the bonding of the fiber and the cementitious material in the composite material, affecting the interaction between the pull-out phenomenon and the extension phenomenon of the fiber in the composite material, thereby affecting the bending properties of the composite material;
[0010] VAE latex powder can adjust the bonding strength of composite materials, and work together with other raw materials to improve the dispersion of limited fibers, improve waterproof, anti-seepage and durability: the introduction of asphalt powder into composite materials will lead to a decrease in the tensile bonding strength of the composite materials. The introduction of VAE latex powder can improve the problem of reduced bonding strength caused by asphalt powder to a certain extent, and on the other hand, it can work together with other raw materials to improve the dispersion of fibers and improve the waterproof, anti-seepage and durability of composite materials;
[0011] Phthalate coupling agents can adjust the bonding between fibers, cementitious materials and aggregates: on the one hand, they can optimize and improve the bending properties of composite materials by adjusting the bonding between different types of high-tenacity fibers, cementitious materials and aggregates; on the other hand, they can improve the freeze-thaw cycle performance, resistance to sulfate erosion and other durability of composite materials by adjusting the bonding force between the three.
[0012] In some preferred embodiments of the asphalt powder fiber cement-based composite material of the present invention, the fiber is one or more of polyvinyl alcohol fiber, modified polypropylene fiber, and ultra-high molecular weight polyethylene fiber.
[0013] In some preferred embodiments of the asphalt powder fiber cement-based composite material of the present invention, the asphalt powder is obtained by emulsifying asphalt, adding a modifier, a stabilizer and a release agent, and then spray-drying the asphalt.
[0014] Emulsifier, modifier and stabilizer are added with water, heated and stirred to mix evenly, then mixed with asphalt according to proportion, and then added with isolation agent and stirred evenly, and asphalt powder is obtained by spray drying.
[0015] In some preferred embodiments of the asphalt powder fiber cement-based composite material of the present invention, the cement is 42.5 silicate cement, 52.5 silicate cement or ordinary silicate cement.
[0016] In some preferred embodiments of the asphalt powder fiber cement-based composite material of the present invention, the river sand is continuously graded river sand with a diameter of less than 1.18 mm.
[0017] In some preferred embodiments of the asphalt powder fiber cement-based composite material of the present invention, the fly ash is primary fly ash with a fineness of 300-400 meshes.
[0018] In some preferred embodiments of the asphalt powder fiber cement-based composite material of the present invention, the water reducer is a polycarboxylate water reducer or a melamine water reducer.
[0019] In some preferred embodiments of the asphalt powder fiber cement-based composite material of the present invention, the phthalate coupling agent is a monoalkoxy titanate coupling agent with a purity greater than 99%.
[0020] Another aspect of the present invention provides a method for preparing an asphalt powder fiber cement-based composite material: weighing the raw material components in proportion, mixing the powder materials evenly at room temperature, adding water, then adding fibers, and mixing evenly to obtain the asphalt powder fiber cement-based composite material.
[0021] Compared with the prior art, the asphalt powder fiber cement-based composite material of the present invention has the following advantages:
[0022] (1) The asphalt powder fiber cement-based composite material of the present invention has excellent mechanical properties, good bending properties, waterproof, anti-seepage and corrosion resistance properties under the compounding effect of multiple raw materials;
[0023] (2) By adding asphalt powder to the asphalt powder fiber cement-based composite material described in the present invention, the dispersion performance of the high-tenacity fiber in the composite material after adding water and stirring, the construction and workability, the corrosion resistance and the bending performance can be improved; by adding VAE latex powder, the bonding strength of the composite material can be adjusted, and the limited fiber dispersion can be improved by synergistic effect with other raw materials, and the waterproof, anti-seepage and durability can be improved; by adding phthalate coupling agent, the combination of fiber, cementitious material and aggregate can be adjusted, and the bending performance, freeze-thaw cycle performance, sulfate corrosion resistance and other durability of the composite material can be optimized and improved. DETAILED DESCRIPTION
[0024] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0025] The present invention will be described in detail below with reference to the embodiments.
[0026] Examples 1 to 3
[0027] In the embodiments described in Examples 1 to 3, unless otherwise specified, the asphalt powder fiber cement-based composite material includes the following raw material components: cement (P.O42.5 ordinary Portland cement), river sand (continuously graded river sand below 1.18 mm), fly ash (first-class fly ash), asphalt powder, VAE latex powder, water reducer (melamine water reducer), phthalate coupling agent (monoalkoxy titanate coupling agent), and fiber (polyvinyl alcohol fiber). The specific proportions are shown in Table 1.
[0028] Table 1 Raw material ratio (Example 1-3)
[0029] Raw material ratio / g cement river sand Fly ash Water reducing agent Latex powder Polyethylene fiber Asphalt powder Phthalate coupling agent Water volume / g Example 1 1000 800 170 4 10 30 10 6 440 Example 2 1000 800 160 4 10 30 20 6 440 Example 3 1000 800 150 4 10 30 30 6 440
[0030] In Table 1, the raw material ratios of Example 1 are as follows by mass percentage: cement 50%, river sand 40%, fly ash 8.5%, water reducer 0.2%, asphalt powder 0.5%, VAE latex powder 0.5%, phthalate coupling agent 0.3%, and polyvinyl alcohol fiber accounts for 1.5% of the total weight of the powder material;
[0031] The raw material ratios of Example 2 are as follows by mass percentage: 50% cement, 40% river sand, 8% fly ash, 0.2% water reducer, 1% asphalt powder, 0.5% VAE latex powder, 0.3% phthalate coupling agent, and polyvinyl alcohol fiber accounts for 1.5% of the total weight of the powder material;
[0032] The raw material ratios of Example 3 are as follows by mass percentage: 50% cement, 40% river sand, 7.5% fly ash, 0.2% water reducer, 1.5% asphalt powder, 0.5% latex powder, 0.3% phthalate coupling agent, and polyvinyl alcohol fiber accounts for 1.5% of the total weight of the powder material;
[0033] Among them, in the implementation methods described in Examples 1 to 3, the preparation process of the asphalt powder fiber cement-based composite material is: weigh the raw materials according to the proportions shown in Table 1, mix the powder materials evenly, add 440g of water, and then add polyvinyl alcohol fibers and stir evenly to obtain the asphalt powder polyvinyl alcohol fiber cement-based composite material.
[0034] The performance of the asphalt powder polyvinyl alcohol fiber cement-based composite materials prepared in Examples 1 to 3 was tested. The test results are shown in Table 2.
[0035] Table 2 Performance indicators (Examples 1-3)
[0036]
[0037] The fibers in Examples 1 to 3 are polyvinyl alcohol fibers: As can be seen from Table 2, as the amount of asphalt powder added in Examples 1 to 3 increases, the setting time of the composite material is prolonged, the equivalent bending toughness, equivalent bending toughness, impermeability pressure resistance and carbonization depth are increased, and the compressive strength and tensile bonding strength properties are reduced.
[0038] Embodiment 4-5
[0039] In the embodiments described in Examples 4 to 5, unless otherwise specified, the asphalt powder fiber cement-based composite material includes the following raw material components: cement (P.O42.5 ordinary Portland cement), river sand (continuously graded river sand below 1.18 mm), fly ash (first-class fly ash), asphalt powder, VAE latex powder, water reducer (melamine water reducer), phthalate coupling agent (monoalkoxy titanate coupling agent), and fiber (polyvinyl alcohol fiber). The specific proportions are shown in Table 3.
[0040] Table 3 Raw material ratio (Example 4-5)
[0041] Raw material ratio / g cement river sand Fly ash Water reducing agent Latex powder Polyethylene fiber Asphalt powder Phthalate coupling agent Water volume / g Example 4 1000 800 165 4 5 30 20 6 440 Example 5 1000 800 155 4 15 30 20 6 440
[0042] In Table 3, compared with Example 2, Examples 4 and 5 adjusted the amount of latex powder and the amount of fly ash (the adjustment of the amount of fly ash is used to balance the change in the amount of latex powder):
[0043] Compared with Example 2, the raw material ratio of Example 4 is that the amount of VAE latex powder is reduced from 0.5% to 0.25%, the amount of fly ash is increased from 8% in Example 2 to 8.25%, and the proportions of other raw materials are the same as in Example 2;
[0044] Compared with Example 2, the raw material ratio of Example 5 is that the amount of VAE latex powder is increased from 0.5% to 0.75%, the amount of fly ash is reduced from 8% in Example 2 to 7.75%, and the proportions of other raw materials are the same as in Example 2;
[0045] In the embodiments 4 to 5, the preparation process of the asphalt powder fiber cement-based composite material is the same as that of embodiments 1 to 3.
[0046] The performance of the asphalt powder polyvinyl alcohol fiber cement-based composite materials prepared in Examples 4 to 5 was tested. The test results are shown in Table 4.
[0047] Table 4 Performance Index (Examples 4-5)
[0048]
[0049] The fibers in Examples 4 to 5 are polyvinyl alcohol fibers. Compared with Example 2, the dosage of VAE latex powder is changed on the basis of Example 2: Based on the performance of Example 2 and the data in Table 4, it can be seen that the change in the dosage of VAE latex powder has little effect on the compressive strength, coagulation time and equivalent bending performance, and the increase in the dosage of latex powder improves the anti-permeability performance, the bonding performance is significantly improved, and the carbonization depth is reduced.
[0050] Embodiment 6-7
[0051] In the embodiments described in Examples 6 to 7, unless otherwise specified, the asphalt powder fiber cement-based composite material includes the following raw material components: cement (P.O42.5 ordinary Portland cement), river sand (continuously graded river sand below 1.18 mm), fly ash (first-class fly ash), asphalt powder, VAE latex powder, water reducer (melamine water reducer), phthalate coupling agent (monoalkoxy titanate coupling agent), and fiber (polyvinyl alcohol fiber). The specific proportions are shown in Table 5.
[0052] Table 5 Raw material ratio (Example 6-7)
[0053] Raw material ratio / g cement river sand Fly ash Water reducing agent Latex powder Polyethylene fiber Asphalt powder Phthalate coupling agent Water volume / g Example 6 1000 800 163 4 10 30 20 3 440 Example 7 1000 800 157 4 10 30 20 9 440
[0054] In Table 5, compared with Example 2, Examples 6 and 7 adjusted the dosage of the phthalate coupling agent and the dosage of the fly ash (the adjustment of the dosage of the fly ash is used to balance the change in the dosage of the phthalate coupling agent):
[0055] Compared with Example 2, the raw material ratio of Example 6 is that the amount of phthalate coupling agent is reduced from 0.3% to 0.15%, the amount of fly ash is increased from 8% in Example 2 to 8.15%, and the proportions of other raw materials are the same as in Example 2;
[0056] Compared with Example 2, the raw material ratio of Example 7 is that the amount of phthalate coupling agent is increased from 0.3% to 0.45%, the amount of fly ash is reduced from 8% in Example 2 to 7.85%, and the proportions of other raw materials are the same as in Example 2;
[0057] In the embodiments 6 to 7, the preparation process of the asphalt powder fiber cement-based composite material is the same as that of embodiments 1 to 3.
[0058] The performance of the asphalt powder polyvinyl alcohol fiber cement-based composite materials prepared in Examples 6 to 7 was tested. The test results are shown in Table 6.
[0059] Table 6 Performance Index (Examples 6-7)
[0060]
[0061] The fibers in Examples 6 to 7 are polyvinyl alcohol fibers. Compared with Example 2, the dosage of the phthalate coupling agent is changed on the basis of Example 2: Based on the performance of Example 2 and the data in Table 6, it can be seen that the increase in the dosage of the phthalate coupling agent has little effect on the coagulation time, impermeability pressure and carbonization depth, and the increase in the dosage of the phthalate coupling agent increases the compressive strength and equivalent bending performance of the material, and improves the tensile bonding strength.
[0062] Embodiments 8 to 10
[0063] In the embodiments described in Examples 8 to 10, unless otherwise specified, the asphalt powder fiber cement-based composite material includes the following raw material components: cement (P.O42.5 ordinary Portland cement), river sand (continuously graded river sand below 1.18 mm), fly ash (first-class fly ash), asphalt powder, VAE latex powder, water reducer (melamine water reducer), phthalate coupling agent (monoalkoxy titanate coupling agent), and fiber (modified polypropylene fiber). The specific proportions are shown in Table 7.
[0064] Table 7 Raw material ratio (Examples 8-10)
[0065] Raw material ratio / g cement river sand Fly ash Water reducing agent Rubber powder Modified polypropylene fiber Asphalt powder Phthalate coupling agent Water volume / g Example 8 1000 800 170 4 10 30 10 6 440 Example 9 1000 800 160 4 10 30 20 6 440 Example 10 1000 800 150 4 10 30 30 6 440
[0066] In Table 7, compared with Examples 1 to 3, Examples 8 to 10 have modified polypropylene fibers, and the ratio and dosage of the powder raw materials are consistent:
[0067] In the embodiments 8 to 10, the preparation process of the asphalt powder fiber cement-based composite material is the same as that of embodiments 1 to 3.
[0068] The performance of the asphalt powder modified polypropylene fiber cement-based composite materials prepared in Examples 8 to 10 was tested. The test results are shown in Table 8.
[0069] Table 8 Performance Index (Examples 8-10)
[0070]
[0071] The fibers in Examples 8 to 10 are modified polypropylene fibers. As can be seen from Table 8, compared with Examples 1 to 3, the equivalent bending performance is significantly improved, the compressive strength is significantly increased, the setting time, impermeability pressure, carbonization depth and tensile bond strength performance indicators are close, and the asphalt powder has a consistent trend in the change of material properties.
[0072] Examples 11 to 13
[0073] In the embodiments described in Examples 11 to 13, unless otherwise specified, the asphalt powder fiber cement-based composite material includes the following raw material components: cement (P.O42.5 ordinary Portland cement), river sand (continuously graded river sand below 1.18 mm), fly ash (first-class fly ash), asphalt powder, VAE latex powder, water reducer (melamine water reducer), phthalate coupling agent (monoalkoxy titanate coupling agent), and fiber (polymer polyethylene fiber). The specific proportions are shown in Table 9.
[0074] Table 9 Raw material ratio (Examples 11-13)
[0075] Raw material ratio / g cement river sand Fly ash Water reducing agent Rubber powder Polyethylene polymer fiber Asphalt powder Phthalate coupling agent Water volume / g Embodiment 11 1000 800 170 4 10 15 10 6 440 Example 12 1000 800 160 4 10 15 20 6 440 Embodiment 13 1000 800 150 4 10 15 30 6 440
[0076] In Table 9, compared with Examples 1 to 3, Examples 11 to 13 have fibers that are high molecular weight polyethylene fibers, and the high molecular weight polyethylene fibers account for 0.75% of the total weight of the powder material, while the proportion and dosage of the powder material are the same:
[0077] In the embodiments 11 to 13, the preparation process of the asphalt powder fiber cement-based composite material is the same as that of embodiments 1 to 3.
[0078] The performance of the asphalt powder polymer polyethylene fiber cement-based composite materials prepared in Examples 11 to 13 was tested. The test results are shown in Table 10.
[0079] Table 10 Performance indicators (Examples 11-13)
[0080]
[0081] The fibers in Examples 11 to 13 are high molecular weight polyethylene fibers. As can be seen from Table 10, as the asphalt powder content increases, the compressive strength decreases, the setting time and tensile bonding decrease, the anti-seepage pressure and carbonization depth performances improve, and the equivalent bending toughness increases with the increase of asphalt powder while the equivalent bending strength decreases.
[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An asphalt powder fiber cement-based composite material, characterized in that: The raw material components include fibers and powder materials, the weight of the fibers is 0.5% to 2% of the weight of the powder materials; the powder materials include the following components by mass percentage: asphalt powder 0.25% to 2.5%, cement 40% to 60%, river sand 30% to 50%, fly ash 5% to 25%, water reducer 0.1% to 0.5%, VAE latex powder 0.25% to 1.0%, and phthalate coupling agent 0.1% to 1.0%.
2. The asphalt powder fiber cement-based composite material according to claim 1, characterized in that: The fiber is one or more of polyvinyl alcohol fiber, modified polypropylene fiber and high molecular polyethylene fiber.
3. The asphalt powder fiber cement-based composite material according to claim 1, characterized in that: The asphalt powder is obtained by emulsifying asphalt, adding a modifier, a stabilizer and an isolating agent, and then spray-drying the asphalt.
4. The asphalt powder fiber cement-based composite material according to claim 1, characterized in that: The cement is 42.5 silicate cement, 52.5 silicate cement or ordinary silicate cement.
5. The asphalt powder fiber cement-based composite material according to claim 1, characterized in that: The river sand is continuously graded river sand below 1.18 mm.
6. The asphalt powder fiber cement-based composite material according to claim 1, characterized in that: The fly ash is primary fly ash.
7. The asphalt powder fiber cement-based composite material according to claim 1, characterized in that: The water reducing agent is a polycarboxylate water reducing agent or a melamine water reducing agent.
8. The asphalt powder fiber cement-based composite material according to claim 1, characterized in that: The phthalate coupling agent is a monoalkoxy titanate coupling agent.
9. The method for preparing the asphalt powder fiber cement-based composite material according to any one of claims 1 to 8, characterized in that: The raw material components are weighed in proportion, the powder materials are mixed evenly at room temperature, water is added, and then fibers are added and mixed evenly to obtain the asphalt powder fiber cement-based composite material.
